ANALISIS PERTIMBANGAN HUKUM HAKIM DALAM PUTUSAN NIET ONTVANKELIJKE VERKLAARD (N.O) NOMOR 18/Pdt.G/2020/Pa.Lbh - NIM. A1011211293, FIERELDA ADINDA (Jurnal Fatwa Hukum, 2025)
AbstractIn Case Number 18/Pdt.G/2020/Pa.Lbh, the panel of judges of the Labuha Religious Court accepted the Defendants' exception on the basis of the consideration that the Plaintiffs' lawsuit lacked parties (plurium litis consortium), the Panel of Judges considered that the lawsuit filed by the Plaintiffs did not involve all parties who should be involved in the case, so it did not meet the formal requirements required in the judicial process, based on this fact the panel of judges then ruled that the lawsuit could not be accepted or Niet Ontvankelijke Verklaard (N.O).   The formulation of the problem in the study is "How is the judge's legal consideration in imposing a Niet Ontvankelijke Verklaard (N.O) decision on Decision Number 18/Pdt.G/2020/Pa.Lbh?". The purpose of this study is to analyze the judge's legal considerations and legal consequences of the N.O decision in case number 18/Pdt.G/2020/Pa.Lbh.The research method used by researchers in this research is the Normative Juridical research method which is descriptive in nature. The problems studied in this research are analyzed through an approach based on the principles in the legal considerations of judges, namely the principle of legal certainty, the principle of justice and the principle of legal expediency. Materials in the research are based on laws and regulations in Indonesia, court decisions, and data sources derived from library materials.The results of this study indicate that the legal considerations of the judge in this case are solely based on the principle of legal certainty which only considers based on the formal defects contained in the lawsuit, namely due to the lack of parties (plurium litis consortium), while the principles of justice and legal expediency have not been reflected in this consideration. The legal consequences of this decision must be seen from both sides of the litigation, for the Plaintiff, the demands for the cancellation of the will and the cancellation of the sale and purchase of the disputed object cannot be fulfilled. As for the Defendant, the decision does not have legal consequences because the Defendant in this decision is only waiting and the rights in the will and sale and purchase of the disputed object are still attached to the Defendant until there is another lawsuit decided by the court which has permanent legal force.Keywords : Decision, Legal Consideration, Niet Ontvankelijke Verklaard  AbstrakDalam Perkara Nomor 18/Pdt.G/2020/Pa.Lbh, majelis hakim Pengadilan Agama Labuha menerima eksepsi para Tergugat dengan dasar pertimbangan bahwa gugatan Para Penggugat kurang pihak (plurium litis consortium), Majelis Hakim menilai bahwa gugatan yang diajukan oleh Para Penggugat tidak melibatkan semua pihak yang seharusnya terlibat dalam perkara, sehingga tidak memenuhi syarat formal yang diperlukan dalam proses peradilan, berdasarkan fakta ini majelis hakim kemudian menjatuhkan putusan gugatan tidak dapat diterima atau Niet Ontvankelijke Verklaard (N.O).   Sehingga, tujuan dari penelitian ini adalah untuk menganalisis pertimbangan hukum hakim dan akibat hukum terhadap putusan N.O dalam perkara nomor 18/Pdt.G/2020/Pa.Lbh.Metode penelitian yang digunakan oleh peneliti dalam penelitian ini adalah metode penelitian Yuridis Normatif yang bersifat deskriptif. Permasalahan yang dikaji dalam penelitian ini dianalisis melalui pendekatan yang berdasarkan pada asas-asas dalam pertimbangan hukum hakim, yaitu asas kepastian hukum, asas keadilan dan asas kemanfaatan hukum. Penelitian ini dianalisis berdasarkan peraturan perundang-undangan di Indonesia, putusan pengadilan, dan sumber data yang berasal dari bahan kepustakaan.Hasil dari penelitian ini menunjukkan bahwa pertimbangan hukum hakim dalam perkara ini semata-mata hanya berdasarkan kepada asas kepastian hukum saja yang hanya mempertimbangkan berdasarkan cacat formil yang terdapat dalam gugatan, yaitu karena kurangnya pihak (plurium litis consortium), sedangkan asas keadilan dan kemanfaatan hukum belum tercermin dalam pertimbangan ini. Adapun akibat hukum dari putusan ini harus dilihat dari kedua belah pihak yang berperkara, bagi pihak Penggugat, tuntutan terhadap pembatalan surat wasiat dan pembatalan jual beli objek sengketa tidak dapat terpenuhi. Sedangkan bagi pihak Tergugat, putusan tersebut tidak mendatangkan akibat hukum karena pihak Tergugat dalam putusan ini sifatnya hanya menunggu dan hak-hak yang ada dalam surat wasiat dan jual beli objek sengketa masih melekat pada pihak Tergugat sampai ada gugatan kembali yang diputus oleh pengadilan yang memiliki kekuatan hukum tetap.Kata Kunci: Niet Ontvankelijke Verklaard, Pertimbangan Hukum, Putusan.